Formulasi & Daya Terima Tuile Tepung Gaplek dengan Ekstrak Bunga Telang sebagai Pewarna Alami - Citra Eka Meliani Dewi; Ade Juwaedah; Cica Yulia (Program Studi Tata Boga Universitas Negeri Jakarta, 2023)
Cookies are a processed food product that has a small shape, crunchy texture and has a long shelf life. The limited mineral content in cookies makes cookies must be added to an ingredient that can increase minerals, namely clam shells. The high content of calcium in clam shells can be used as an option in making cookies. This study aims to analyze the chemical, physical and sensory properties of cookies added with different types of shellfish flour. The experimental design used was a completely randomized design (CRD) with treatment of 3 different types of clam shell flour, namely batik clam shell flour, blood clam shell flour, and green mussel shell flour. The test results showed that the control cookies were not significantly different from cookies with the addition of batik clam shell flour, cookies with the addition of blood clam shell flour, and cookies with the addition of green mussel shell flour. The data were analyzed using Analysis of Diversity (ANOVA), if there is a difference, then proceed with the DMRT test with a 95% confidence level with SPSS 21 computer software. While cookies with the addition of batik clam shell flour were significantly different from cookies with the addition of blood clam shell flour and cookies with the addition of green mussel shell flour. The addition of clam shell flour had a significant effect on the ash content of cookies. The addition of clam shell flour causes the color of the cookies to be darker. Descriptive organoleptic testing of cookies with the addition of clam shell flour did not have a significant effect on control cookies. Hedonic organoleptic testing of cookies with the addition of clam shell flour did not have a significant effect on the color, taste, aroma, and texture of cookies.